Knowledge of residents about Chagas disease and its vectors in a municipality of Juruá, Amazonas - da Silva, Luciana Braga; da Silva Moura, Manoella; Madeir, Fernanda Portela; Florencio, Wilame Germano; Prolo, Sergio Luiz; Ribeiro, Mariane Albuquerque Lima [UNESP]; de Oliveira, Jader; de Oliveira Meneguetti, Dionatas Ulises (Faculdade de Filosofia e Ciências, 2024)
Introduction: Chagas disease (CD) is an infectious condition caused by the protozoan Trypanosoma cruzi, primarily transmitted by vectors. Understanding the diversity of these vectors in a region is crucial for disease prophylaxis, with vector control being the main measure to reduce its incidence. Therefore, it is essential to enhance knowledge about triatomines to guide prevention and promotion actions, with active community participation. Objective: to describe residents’ knowledge about Chagas disease and its vectors in a municipality in the Western Amazon of Brazil. Methods: the data was collected by means of an interview with the application of a semi-structured questionnaire containing objective and subjective questions to residents over 18 years of age in the urban area of the municipality of Guajará - AM in their homes. Results: out of 400 participants, 75% reported having heard of Triatomines. 65.38% of those who encountered a suspected insect in their home or surroundings claimed to have killed it and most could not indicate where the insect should be taken (91.25%). Only 40.25% correctly identified the triatomines, with Rhodnius montenegrensis (22.75%) being the most chosen. Most were unaware of signs/symptoms (70.25%), transmission routes (52.75%), and preventive measures (62.5%) related to CD. Regarding dietary habits: 93% consumed açaí (Euterpe olerácea), 88.75% buriti (Mauritia flexuosa), 65.5% sugarcane (Saccharum officinarum), 50.5% bacaba (Oenocarpus bacaba), 50.25% patoá (Oenocarpus bataua), and 75.75% game meat. Conclusion: the research revealed several knowledge gaps on the topic, emphasizing the need to intensify health education actions.
Keywords: community participation; health education; public health surveillance; Triatominae